Moisture condensation on building envelopes in differential ventilated spaces in the tropics: quantitative assessment of influencing factors - Ali, Maisarah; Oladokun, Majeed; Osman, Samsul Bahrin; Samsuddin, Niza; Hamzah, Hairul Aini (EDP Sciences, 2016)
Ventilation systems play a significant role in maintaining the indoor thermal and hygric balance. Nevertheless, the systems had been implicated to result in many problems. In the tropical climate, especially for energy efficiency purposes, building spaces are operated with differential ventilation. Such spaces operate on 24-hrs basis, some on 8-hrs while others are either naturally ventilated or served with mechanical supply-exhaust fan systems with non-conditioned outdoor air. This practice had been found to result in condensation problems. This study involves a quantitative appraisal of the effect of operative conditions and hygrothermal quality of building envelopes on condensation risk. The in-situ experiment is combined with an analytical approach to assessing the hygrothermal quality of building envelopes in a tropical climate building under differential ventilation between adjacent spaces. The case-studied building is with a known history of condensation and associated damages including mould growth. The microclimate measurement and hygrothermal performance of the wall and floor against condensation and mould growth risks had been previously reported elsewhere. As a step further, the present study evaluates the effects of various envelope insulation types and configurations together with the HVAC cooling set-points on envelope hygrothermal performance. The results revealed that overcooling the air-conditioned side increases condensation risk on the non-air-conditioned side of the envelopes. The envelopes failed criteria for surface condensation at existing operative conditions irrespective of envelope hygrothermal quality improvements. However, the envelope performed well at improved cooling operative conditions even at existing envelope hygrothermal quality. It is, therefore, important to ascertain the envelope hygrothermal quality as well the cooling operative conditions while embarking on energy efficiency operations in mechanical ventilation systems under differential ventilation.